A kind of hollow porous gold nanoparticle and its preparation method and application

By generating nanoPbS templates in aqueous solution and using surfactant-mediated gold deposition and etching technology, hollow porous gold nanoparticles were prepared, solving the problem of unsatisfactory conversion and selectivity of the catalytic reaction in the prior art, and achieving efficient and controllable catalytic effect.

CN118951039BActive Publication Date: 2025-03-21NANKAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411440828.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare simple, efficient and controllable single metal hollow porous gold nanoparticles, resulting in unsatisfactory conversion and selectivity of catalytic reactions.

Method used

Hollow porous gold nanoparticles are formed by generating nanoPbS templates in aqueous solution and deposition and etching with gold salt and ascorbic acid under the guidance of surfactant.

Benefits of technology

Controllable synthesis of hollow porous gold nanoparticles is achieved, template residues and structural instability are avoided, and catalytic function and reaction controllability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118951039B_ABST
    Figure CN118951039B_ABST
Patent Text Reader

Abstract

The present invention relates to a hollow porous gold nanoparticle and a preparation method and application thereof. First, a regular octahedral PbS is prepared as a template. Under the mediation of a surfactant, hexadecyltrimethylammonium chloride, ascorbic acid rapidly reduces and deposits a gold salt on the template surface to form multiple nucleation sites. The PbS template is synchronously etched during the gold deposition growth process. The cavity and multi-porous channel structure of the gold nanoparticle are constructed based on the dynamic mass transfer process of growth-etching. The preparation method has good controllability and repeatability, can realize the controllable synthesis of the overall size and internal cavity size of the hollow porous gold nanoparticle, the prepared gold nanoparticle has good dispersibility and uniform size, and can be applied to catalysts, optical sensors, biomaterials and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to the preparation of gold nanoparticles with a nano-scale microstructure, which can be used in the field of photocatalysis. Background Art

[0002] Compared with bulk gold materials, colloidal gold nanoparticles, like other nanomaterials, have small size effects, surface effects, quantum size effects, and macroscopic quantum tunneling effects due to the reduction of particle size to the nanoscale, which endows gold nanoparticles with special properties in magnetism, light, and electricity. Therefore, colloidal gold nanoparticles show potential application prospects in optoelectronic devices, optical sensing, nanocatalysis, biomedicine, and other fields. In addition, due to the high surface energy and unsaturated coordination of the surface atoms of gold nanoparticles, and the high-index crystal planes that provide abundant catalytic active centers, they have high catalytic activity. However, in heterogeneous catalytic reactions driven by gold-based nanoparticles, the catalytic behavior of molecules at the nanoscale is often disordered due to the different interaction relationships between reactants and active sites. In addition, catalytic reactions are highly sensitive to the nanostructure of catalytic materials, and any slight structural changes may lead to different catalytic reaction paths. These factors make heterogeneous catalysis driven by gold-based nanoparticles inherently uncontrollable to a certain extent, resulting in unsatisfactory conversion and selectivity of the reaction.

[0003] In recent years, metal nanocatalysts with hollow porous structures have become an ideal nanoreactor. Compared with the bulk dense structure, its internal nanocavity combined with the interconnected controllable multi-porous shell structure has a higher specific surface area and lower density, which is conducive to increasing the contact and collision probability between the reactant molecules and the catalyst surface. At the same time, the nanocavity and shell pore structure have a confinement effect, which provides potential opportunities for molecular diffusion, adsorption and surface reaction, and promotes the mass transfer effect and permeability of the catalytic process. In addition, the active sites can be flexibly constructed in the cavity or shell pore according to the reaction requirements, which provides more abundant catalytic centers, further optimizes the electronic and spatial effects of the catalyst, and thus greatly improves the catalytic conversion rate and selectivity of the target product. Therefore, it can be foreseen that with the development of nanotechnology, hollow porous colloidal gold nanoparticles will receive more and more attention in related research fields.

[0004] At present, the preparation of hollow porous metal nanostructures is mainly through polymer template method, Kirkendall effect, alloy galvanic replacement method, etc. However, the residual polymer template often shields the catalytic sites, and the removal of the template easily leads to structural instability, inducing nanoparticles to agglomerate. The synthesis process based on the Kirkendall effect and alloy galvanic replacement mechanism requires the participation of multiple metals in the reaction, and the preparation process is relatively complicated. The etching of sacrificial metals easily leads to the difficulty in controlling the uniformity of the nanoparticle structure and composition, and the cost is relatively high. Therefore, it is of great significance to develop a simple, efficient and controllable method for synthesizing single metal hollow porous gold nanoparticles. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a hollow porous gold nanoparticle and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is: a method for preparing hollow porous gold nanoparticles, comprising the following steps:

[0007] Step 1: In an aqueous solution, thioacetamide, hexadecyltrimethylammonium bromide, lead acetate and acetic acid are reacted to generate a nano-PbS template;

[0008] Step 2: using surfactant hexadecyltrimethylammonium chloride as a ligand, adding gold salt, PbS template, and reducing agent ascorbic acid, mixing well and then standing to react;

[0009] Step 3: Collect the solid material obtained by the reaction, add PbS template etchant, and obtain hollow porous gold nanoparticles after sufficient reaction.

[0010] Preferably, in step 1, the molar ratio of thioacetamide, hexadecyltrimethylammonium bromide, lead acetate and acetic acid is 0.4-0.72: 0.09-0.144: 0.39-0.43: 0.6-0.81.

[0011] Preferably, the mixed solution in step 1 is placed in an environment of 70-80° C. for reaction for 5-10 hours.

[0012] Preferably, in step 2, the molar ratio of deionized water: hexadecyltrimethylammonium chloride: gold salt: ascorbic acid is 1000: 1.44–3.6: 0.0045–0.0135: 0.045–0.18; the mass ratio of deionized water: PbS template is 1000: 4.5–9.

[0013] Preferably, in step 2, the reaction temperature is 25-35°C and the reaction is allowed to stand for 12-72 hours.

[0014] Preferably, the gold salt is a combination of one or more of chloroauric acid, chloroauric acid trihydrate and chloroauric acid tetrahydrate.

[0015] Preferably, in step three, the sample is centrifuged to remove the supernatant, an equal volume of a PbS template etchant is added, and after ultrasonic dispersion, the mixture is allowed to react for 0.5-5 h; the PbS template etchant is dilute hydrochloric acid or hydrogen peroxide with a molar concentration of 50-200 mM.

[0016] The hollow porous gold nanoparticles are prepared by the method for preparing the hollow porous gold nanoparticles.

[0017] Application of gold nanoparticles in catalysts.

[0018] Preferably, the photocatalytic selective hydrogenation reduction of p-chloronitrobenzene to prepare p-chloroaniline comprises the following specific steps:

[0019] Step 1: The synthesized gold nanoparticles are dispersed in a reactor containing a deionized water and anhydrous ethanol system in a volume ratio of 1:1, nitrogen is introduced to exclude oxygen, and p-chloronitrobenzene and hydrazine hydrate are added in sequence under stirring; wherein the molar ratio of deionized water: p-chloronitrobenzene is 1000:0.18-0.72; the volume ratio of deionized water: hydrazine hydrate is 1:0.02-0.1;

[0020] Step 2: The reaction system is controlled to room temperature using an external circulating condensing water system and placed under a 300 W xenon lamp for 1–5 h.

[0021] Step 3: The reaction solution is centrifuged to remove the gold nanoparticles, and the product is extracted with dichloromethane and then analyzed by gas chromatography-mass spectrometry.

[0022] The advantages and positive effects of the present invention are: constructing a PbS template to participate in the growth of gold nanoparticles, and the H contained in the gold salt in the growth solution + With the Cl in the surfactant – The PbS template is etched synchronously during the gold deposition and growth process by combining with dilute hydrochloric acid, and a multi-porous structure of gold nanoparticles is formed based on the dynamic mass transfer process of growth-etching. Such a treatment method can completely remove the PbS template, avoid shielding the catalytic sites, and will not destroy the constructed multi-porous structure, thus avoiding the agglomeration of nanoparticles.

[0023] The size of the PbS template can be adjusted by controlling the reaction conditions, thereby adjusting the size of the inner cavity of the gold nanoparticles. The prepared gold nanoparticles have good dispersibility and uniform size. The method of the present invention is simple to operate and has good controllability and repeatability.

[0024] The prepared hollow porous gold nanoparticles have an absorption spectrum covering the visible-near infrared region and a high specific surface area, and can be used in catalysts, optical sensors, biomaterials and other fields; when used as catalysts, they can have a high catalytic function. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Scanning electron microscope (SEM) image of the hollow porous gold nanoparticles prepared in Example 1;

[0026] Figure 2 High-angle annular dark field scanning transmission (HAADF-STEM) image of the hollow porous gold nanoparticles prepared in Example 1;

[0027] Figure 3 UV-visible absorption spectrum of the hollow porous gold nanoparticles prepared in Example 1;

[0028] Figure 4 Scanning electron microscope (SEM) image of the gold nanoparticles prepared in Comparative Example 5. DETAILED DESCRIPTION

[0029] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0030] The invention relates to a hollow porous gold nanoparticle and a preparation method and application thereof. First, a regular octahedral PbS is prepared as a template. Under the mediation of a surfactant, hexadecyltrimethylammonium chloride, ascorbic acid rapidly reduces and deposits a gold salt on the template surface to form a plurality of nucleation sites. The PbS template is synchronously etched during the gold deposition growth process, and a cavity and a multi-porous channel structure of the gold nanoparticle are constructed based on a growth-etching dynamic mass transfer process. The preparation method has good controllability and repeatability, and can realize controllable synthesis of the overall size and internal cavity size of the hollow porous gold nanoparticle. On the one hand, by adjusting the size of the PbS template, internal cavities of different sizes can be obtained. On the other hand, by adjusting the amount of the PbS template, the amount of the gold salt and the amount of ascorbic acid added, the overall size and pore distribution of the hollow porous gold nanoparticle can be regulated. The prepared gold nanoparticles have good dispersibility and uniform size.

[0031] The preparation method of hollow porous gold nanoparticles comprises the following steps:

[0032] Step 1: Add deionized water to a centrifuge tube, then add thioacetamide, hexadecyltrimethylammonium bromide, lead acetate and acetic acid in sequence, mix the solution evenly, place it in a 70-80 °C constant temperature water bath and react for 5-10 h to grow a regular octahedral PbS template; wherein the molar ratio of deionized water: thioacetamide: hexadecyltrimethylammonium bromide: lead acetate: acetic acid is 1000: 0.4-0.72: 0.09-0.144: 0.39-0.43: 0.6-0.81;

[0033] Step 2: Add hexadecyltrimethylammonium chloride to deionized water, heat and stir to dissolve, then cool to room temperature, add gold salt, add octahedral PbS template and ascorbic acid in sequence under vigorous stirring, stop stirring after 5-10 minutes, and then place the sample in a constant temperature water bath at 25-35 °C for 12-72 hours; wherein, the molar ratio of deionized water: hexadecyltrimethylammonium chloride: gold salt: ascorbic acid is 1000: 1.44-3.6: 0.0045-0.0135: 0.045-0.18; the mass ratio of deionized water: PbS template is 1000: 4.5-9;

[0034] Wherein, the gold salt is a combination of one or more of chloroauric acid, chloroauric acid trihydrate and chloroauric acid tetrahydrate;

[0035] Step 3: The sample is centrifuged to remove the supernatant, and the same volume of PbS template etchant as the supernatant is added. After ultrasonic dispersion, the sample is allowed to react for 0.5-5 h, and the supernatant is removed by centrifugation again. The same volume of deionized water is added for dispersion and storage;

[0036] The PbS template etchant is dilute hydrochloric acid or hydrogen peroxide with a molar concentration of 50–200 mM.

[0037] In the preparation method, a regular octahedral PbS template is first constructed. Acetic acid is added to the PbS template to adjust the pH of the reaction system to close to 4.0. In a weakly acidic environment, thioacetamide is decomposed by heating in a water bath to release S 2– , and with Pb 2+ The surfactant hexadecyltrimethylammonium bromide controls the formation of the (111) surface of PbS nanocrystals to generate nano-PbS templates. The size of the PbS template can be controlled by the concentration of the precursors thioacetamide and lead acetate, the water bath temperature, and the growth time. By controlling the size of the PbS template, the shape and size of the pores of the gold nanoparticles can be controlled.

[0038] The growth of hollow porous gold nanoparticles uses the surfactant hexadecyltrimethylammonium chloride as a ligand. The gold salt in the growth solution contains H + With the Cl in the surfactant – The gold salt precursor is AuCl in the form of dilute hydrochloric acid, which is used to etch the PbS template synchronously during the gold deposition and growth process. Based on the dynamic mass transfer process of growth-etching, the multi-porous structure of gold nanoparticles is formed. 4–The gold nanoparticles exist in the form of gold atoms, which are more easily reduced to gold atoms and form multiple nucleation sites, which is conducive to the formation of a multi-porous structure. During the growth of gold nanoparticles, the molar ratio of the reducing agent ascorbic acid to the gold salt is always controlled to be greater than or equal to 10:1. Excess ascorbic acid can drive the gold salt to be rapidly reduced to form multiple nucleation sites, thereby generating a multi-porous structure.

[0039] The method of the present invention has good controllability and repeatability, and can realize the controllable synthesis of the overall size and internal cavity size of hollow porous gold nanoparticles. On the one hand, by adjusting the size of the PbS template, internal cavities of different sizes can be obtained. On the other hand, by adjusting the amount of the PbS template, the amount of gold salt and ascorbic acid added, the overall size and pore distribution of the hollow porous gold nanoparticles can be regulated. The prepared gold nanoparticles have good dispersibility and uniform size.

[0040] The hollow porous gold nanoparticles prepared by the above method have uniform pores and a high specific surface area. The gold nanoparticles have an absorption spectrum that can cover the visible-near infrared light region and a wide light absorption range. Based on the above characteristics, the gold nanoparticles can be used in catalysts, optical sensors, biomaterials and other fields.

[0041] In certain embodiments of the present invention, the prepared hollow porous gold nanoparticles can be used for photocatalytic selective hydrogenation reduction of p-chloronitrobenzene to prepare p-chloroaniline, and the specific steps are as follows:

[0042] Step 1: The synthesized gold nanoparticles are dispersed in a reactor containing a deionized water / anhydrous ethanol (volume ratio 1:1) system, nitrogen is introduced to exclude oxygen, and p-chloronitrobenzene and hydrazine hydrate are added in sequence under stirring; wherein the molar ratio of deionized water: p-chloronitrobenzene is 1000:0.18–0.72; the volume ratio of deionized water: hydrazine hydrate is 1:0.02–0.1;

[0043] Step 2: The reaction system is controlled to room temperature using an external circulating condensing water system and placed under a 300 W xenon lamp for 1-5 h;

[0044] Step 3: The reaction solution is centrifuged to remove the gold nanoparticles, and the product is extracted with dichloromethane and then analyzed by gas chromatography-mass spectrometry.

[0045] It can be verified that the hollow porous gold nanoparticles prepared by the method of the present invention show high conversion rate and high selectivity in the photocatalytic selective hydrogenation reduction of p-chloronitrobenzene to prepare p-chloroaniline, proving that it has efficient catalytic ability.

[0046] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.

[0047] Example 1

[0048] This embodiment relates to a method for preparing hollow porous gold nanoparticles, and the specific steps are as follows:

[0049] (1) Deionized water was added to a centrifuge tube, and then thioacetamide, hexadecyltrimethylammonium bromide, lead acetate, and acetic acid were added in sequence; wherein the molar ratio of deionized water: thioacetamide: hexadecyltrimethylammonium bromide: lead acetate: acetic acid was 1000: 0.4: 0.1: 0.4: 0.8; the solution was mixed evenly and placed in an 80°C water bath for 8 h to react, thereby growing an octahedral PbS template;

[0050] (2) Add hexadecyltrimethylammonium chloride to deionized water, heat and stir at 50°C to dissolve, then cool to room temperature, add chloroauric acid trihydrate, add the above-mentioned octahedral PbS template under vigorous stirring, and then add ascorbic acid. Stop stirring after 5 minutes, place in a 30°C water bath and let react for 12 hours; wherein the molar ratio of deionized water: hexadecyltrimethylammonium chloride: gold salt: ascorbic acid is 1000:1.67:0.008:0.08; the mass ratio of deionized water: PbS template is 1000:4.5;

[0051] (3) The sample was centrifuged at 5000 rpm for 3 min to remove the supernatant, and an equal volume of 0.1 M dilute hydrochloric acid was added. After ultrasonic dispersion, the sample was allowed to stand for 30 min, and then centrifuged at 5000 rpm for 3 min to remove the supernatant. An equal volume of deionized water was added to disperse and store the sample. The resulting gold nanoparticles were numbered AuNP-1.

[0052] The scanning electron microscope (SEM) image and high-angle annular dark field scanning transmission (HAADF-STEM) image of the hollow porous gold nanoparticles prepared in this example are shown in Figure 1 and Figure 2 As can be seen from the figure, the prepared gold nanoparticles are spherical in shape, well dispersed, with internal cavities and uniform multi-porous shell structures. In addition, the UV-visible absorption spectrum of the gold nanoparticles is shown in Figure 3 , indicating that the hollow porous structure has an absorption spectrum covering the visible-near infrared region.

[0053] Example 2

[0054] The preparation steps of Example 2 are the same as those of Example 1, except that the amounts of the components in step (1) are changed to deionized water: thioacetamide: hexadecyltrimethylammonium bromide: lead acetate: acetic acid, and the molar ratio is changed to 1000: 0.72: 0.144: 0.43: 0.81. The resulting gold nanoparticles are numbered AuNP-2.

[0055] Example 3

[0056] The preparation steps of Example 3 are the same as those of Example 1, except that the static reaction time in the constant temperature water bath in step (1) is changed from 8 h to 5 h, in order to reduce the size of the regular octahedral PbS template, thereby regulating the internal cavity size of the gold nanoparticles. The obtained gold nanoparticles are numbered AuNP-3.

[0057] Example 4

[0058] The preparation steps of Example 4 are the same as those of Example 1, except that the amounts of gold salt and ascorbic acid in step (2) are respectively changed to: the amount of deionized water remains unchanged, and the molar ratio of deionized water: gold salt: ascorbic acid is 1000:0.0135:0.18. The obtained gold nanoparticles are numbered AuNP-4.

[0059] Example 5

[0060] The preparation steps of Example 5 are the same as those of Example 1, except that the mass ratio of deionized water:PbS template in step (2) is changed from 1000:4.5 to 1000:9, thereby reducing the overall size of the hollow porous gold nanoparticles. The obtained gold nanoparticles are numbered AuNP-5.

[0061] Example 6

[0062] The preparation steps of Example 6 are the same as those of Example 1, except that the static growth time in the constant temperature water bath in step (2) is changed to 72 h. The obtained gold nanoparticles are numbered AuNP-6.

[0063] Example 7

[0064] The preparation steps of Example 7 are the same as those of Example 1, except that the PbS template etchant dilute hydrochloric acid in step (3) is replaced by hydrogen peroxide. The obtained gold nanoparticles are numbered AuNP-7.

[0065] Comparative Example 1

[0066] The purpose is to compare with Example 1 to illustrate the effect of the concentrations of thioacetamide and lead acetate on the morphology and structure of the PbS template and the deposition and growth of gold nanoparticles.

[0067] The preparation steps of Comparative Example 1 are the same as those of Example 1, except that the amounts of thioacetamide and lead acetate in step (1) are changed to: the molar ratio of deionized water: thioacetamide: lead acetate is 1000:0.8:0.8, and the obtained gold nanoparticles are numbered AuNP-8.

[0068] Comparative Example 2

[0069] The purpose is to compare with Example 1 to illustrate the effect of adjusting the pH of the reaction system with acetic acid on the growth of the PbS template.

[0070] The preparation steps of Comparative Example 2 are the same as those of Example 1, except that the amount of acetic acid in step (1) is changed to a molar ratio of deionized water: acetic acid of 1000:1.6. The obtained gold nanoparticles are numbered AuNP-9.

[0071] Comparative Example 3

[0072] The purpose is to compare with Example 1 to illustrate the necessity of controlling the reaction temperature for the growth of the PbS template.

[0073] The preparation steps of Comparative Example 3 are the same as those of Example 1, except that the temperature of the constant temperature water bath reaction in step (1) is adjusted to 50° C. The obtained gold nanoparticles are numbered AuNP-10.

[0074] Comparative Example 4

[0075] The purpose is to compare with Example 1 to illustrate the effect of constant temperature reaction time on the morphology and structure of the PbS template and the deposition and growth of gold nanoparticles.

[0076] The preparation steps of Comparative Example 4 are the same as those of Example 1, except that the constant temperature water bath reaction time in step (1) is shortened to 4 h. The obtained gold nanoparticles are numbered AuNP-11.

[0077] Comparative Example 5

[0078] The purpose is to compare with Example 1 to illustrate the effect of the choice of surfactant on the formation of shell pore structure during the growth of gold nanoparticles.

[0079] The preparation steps of Comparative Example 5 are the same as those of Example 1, except that the surfactant used in step (2) is replaced by hexadecyltrimethylammonium bromide. The obtained gold nanoparticles are numbered AuNP-12. The scanning electron microscope (SEM) image of the prepared gold nanoparticles is as follows: Figure 4 As shown in the figure, it can be seen that the prepared gold nanoparticles have a dense shell layer and a non-porous structure, which indicates that different types of surfactants will affect the morphology of the prepared gold nanoparticles.

[0080] Comparative Example 6

[0081] The purpose is to compare with Example 1 to illustrate the effect of the amount of PbS template on the deposition and growth of gold nanoparticles.

[0082] The preparation steps of Comparative Example 6 are the same as those of Example 1, except that the mass ratio of ionized water:PbS template in step (2) is changed from 1000:4.5 to 1000:18, and the obtained gold nanoparticles are numbered AuNP-13.

[0083] Comparative Example 7

[0084] The purpose is to compare with Example 1 to illustrate the effect of ascorbic acid dosage on the morphology and structure of gold nanoparticles.

[0085] The preparation steps of Comparative Example 7 are the same as those of Example 1, except that the amount of ascorbic acid in step (2) is changed to a molar ratio of deionized water: ascorbic acid of 1000:0.02. The obtained gold nanoparticles are numbered AuNP-14.

[0086] Comparative Example 8

[0087] The purpose is to compare with Example 1 to illustrate the necessity of controlling the reaction temperature for the deposition and growth of gold nanoparticles.

[0088] The preparation steps of Comparative Example 8 are the same as those of Example 1, except that the temperature of the constant temperature water bath reaction in step (2) is adjusted to 50° C. The obtained gold nanoparticles are numbered AuNP-15.

[0089] Comparative Example 9

[0090] The purpose is to compare with Example 1 to illustrate the effect of constant temperature reaction time on the growth of gold nanoparticles.

[0091] The preparation steps of Comparative Example 9 are the same as those of Example 1, except that the constant temperature water bath reaction time in step (2) is shortened to 3 h. The obtained gold nanoparticles are numbered AuNP-16.

[0092] Comparative Example 10

[0093] The purpose is to make a comparison with Example 1 to illustrate the necessity of using a PbS template etchant.

[0094] The preparation steps of Comparative Example 10 are the same as those of Example 1, except that the etching step in step (3) is omitted, and the PbS template etchant is not used. The nanoparticles are directly dispersed in deionized water for storage, and the subsequent steps remain unchanged. The obtained gold nanoparticles are numbered AuNP-17.

[0095] Example 8: Application of gold nanoparticles in the photocatalytic selective hydrogenation reduction of p-chloronitrobenzene to prepare p-chloroaniline

[0096] The gold nanoparticles prepared in Examples 1-7 and Comparative Examples 1-10 were respectively applied to a method for preparing p-chloroaniline by photocatalytic selective hydrogenation reduction of p-chloronitrobenzene. The specific operation process and conditions are as follows:

[0097] (1) Disperse 2 mL of synthesized gold nanoparticles in a reactor containing 8 mL of a mixed solution of deionized water / anhydrous ethanol (volume ratio 1:1), introduce nitrogen to exclude oxygen, and add 0.1 mmol of p-chloronitrobenzene and 0.1 mL of hydrazine hydrate in sequence under stirring;

[0098] (2) The reaction system was controlled to room temperature using an external circulating condensing water system and placed under 300 W xenon lamp for 5 h.

[0099] (3) The reaction solution is centrifuged to remove the gold nanoparticles, and the product is extracted with dichloromethane and analyzed by gas chromatography-mass spectrometry.

[0100] The activity evaluation results of different gold nanoparticles in the selective hydrogenation of p-chloronitrobenzene under 300 W xenon lamp irradiation are shown in Table 1.

[0101] Table 1

[0102]

[0103] From the data in Table 1, it can be seen that the prepared gold nanoparticles can be used to catalyze the selective hydrogenation reaction of p-chloronitrobenzene. Controlling the raw material mixing ratio, controlling the ligand type, reaction temperature and other reaction conditions can significantly affect the structure of the gold nanoparticles, thereby affecting its catalytic performance in the catalytic reaction. In particular, by comparing the experimental results of Examples 1-7 and Examples 8-17, it can be seen that the gold nanoparticles prepared in Examples 1-7 have both a high conversion rate and a high selectivity in the selective hydrogenation reaction of p-chloronitrobenzene.

[0104] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing hollow porous gold nanoparticles, characterized in that: The steps include: Step 1: In an aqueous solution, thioacetamide, hexadecyltrimethylammonium bromide, lead acetate and acetic acid are reacted to generate a nano-PbS template, and the mixed solution is placed in an environment of 70-80°C for reaction for 5-10 hours; the molar ratio of thioacetamide, hexadecyltrimethylammonium bromide, lead acetate and acetic acid is 0.4-0.72: 0.09-0.144: 0.39-0.43: 0.6-0.81; Step 2: Using surfactant hexadecyltrimethylammonium chloride as a ligand, add gold salt, PbS template, and reducing agent ascorbic acid, mix thoroughly and let stand, and react at 25-35 °C for 12-72 h; the molar ratio of deionized water: hexadecyltrimethylammonium chloride: gold salt: ascorbic acid is 1000: 1.44-3.6: 0.0045-0.0135: 0.045-0.18; The mass ratio of deionized water: PbS template is 1000:4.5–9; the H contained in the gold salt + ; Step 3: Collect the solid material obtained by the reaction, add the PbS template etchant, centrifuge the sample to remove the supernatant, add the PbS template etchant of the same volume as the supernatant, and let it react for 0.5-5 h after ultrasonic dispersion; the PbS template etchant is dilute hydrochloric acid or hydrogen peroxide with a molar concentration of 50-200 mM; after sufficient reaction, hollow porous gold nanoparticles are obtained, and the gold nanoparticles have cavities and multiple channels.

2. The method for preparing hollow porous gold nanoparticles according to claim 1, characterized in that: The gold salt is a combination of one or more of chloroauric acid, chloroauric acid trihydrate and chloroauric acid tetrahydrate.

3. The hollow porous gold nanoparticles prepared by the method for preparing the hollow porous gold nanoparticles according to claim 1 or 2.

4. Use of the gold nanoparticles according to claim 3 in catalysts.

5. The use according to claim 4, characterized in that: It is used for photocatalytic selective hydrogenation reduction of p-chloronitrobenzene to prepare p-chloroaniline, and the specific steps are as follows: Step 1: The synthesized gold nanoparticles are dispersed in a reactor containing a deionized water and anhydrous ethanol system in a volume ratio of 1:1, nitrogen is introduced to exclude oxygen, and p-chloronitrobenzene and hydrazine hydrate are added in sequence under stirring; wherein the molar ratio of deionized water: p-chloronitrobenzene is 1000:0.18-0.72; the volume ratio of deionized water: hydrazine hydrate is 1:0.02-0.1; Step 2: The reaction system is controlled to room temperature using an external circulating condensing water system and placed under a 300 W xenon lamp for 1–5 h. Step 3: The reaction solution is centrifuged to remove the gold nanoparticles, and the product is extracted with dichloromethane and then analyzed by gas chromatography-mass spectrometry.

Citation Information

Patent Citations

  • Mesoporous carbon-loaded gold nano catalyst and application thereof

    CN102553583A

  • Gold nano-particle cup, gold nano-particle bottle and preparation method of gold nano-particle cup and gold nano-particle bottle

    CN106392096A

  • Porous gold nano-spheres, preparation method of porous gold nano-spheres as well as intermediate product gold lead sulfide hybrid nanostructure

    CN107335812A